The Digital Behavioral Patterns and Preferences of Millennials within Indonesia's Political Digital Landscape: A Case Study - Fauzi, Reza; Maryana, Ina; Milah, Asep Irfan Saeful; Busro; Hilmi, Fuad; Paujiah, Epa; Mulyana, Rohmat (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study investigates the interaction dynamics between Indonesian millennials and digital media platforms, particularly within the political context. Utilizing a mixed-methods approach, surveys were conducted among individuals aged 15 to 18, complemented by focus group discussions. The study examined their comprehension of digital media, content consumption preferences, and proficiency in digital literacy, with data analyzed using Excel 2021. The findings indicate that Indonesian millennials possess a profound understanding of digital media, exhibiting a strong preference for entertainment-oriented content such as movies, text messages, and digital videos. Concurrently, they continue to engage with political news via online media platforms and television broadcasts. The study also reveals a high level of awareness among millennials regarding the significance of digital literacy, reflecting their adeptness in critically evaluating and validating information sources. These outcomes provide significant insights into millennials' potential contributions to digital politics, underscoring their status as engaged citizens in the digital.